2021
DOI: 10.3389/fnhum.2021.633655
|View full text |Cite
|
Sign up to set email alerts
|

Closed-Loop Deep Brain Stimulation to Treat Medication-Refractory Freezing of Gait in Parkinson’s Disease

Abstract: Background: Treating medication-refractory freezing of gait (FoG) in Parkinson’s disease (PD) remains challenging despite several trials reporting improvements in motor symptoms using subthalamic nucleus or globus pallidus internus (GPi) deep brain stimulation (DBS). Pedunculopontine nucleus (PPN) region DBS has been used for medication-refractory FoG, with mixed findings. FoG, as a paroxysmal phenomenon, provides an ideal framework for the possibility of closed-loop DBS (CL-DBS).Methods: In this clinical tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 53 publications
(75 reference statements)
0
25
0
Order By: Relevance
“…Closed-loop work incorporating PPN-DBS have also begun but appear more problematic. One recent study implanted five medication-refractory FOG PD patients with two closed-loop PPN leads in addition to bilateral globus pallidus interna (GPi) leads ( Molina et al, 2021 ). However, due to surgical complications, two of these patients needed explantation of the leads.…”
Section: Surgical Approachesmentioning
confidence: 99%
“…Closed-loop work incorporating PPN-DBS have also begun but appear more problematic. One recent study implanted five medication-refractory FOG PD patients with two closed-loop PPN leads in addition to bilateral globus pallidus interna (GPi) leads ( Molina et al, 2021 ). However, due to surgical complications, two of these patients needed explantation of the leads.…”
Section: Surgical Approachesmentioning
confidence: 99%
“…To overcome these and other limitations of cDBS, responsive DBS (rDBS) has been introduced and relies on one or more feedback signals to modulate stimulation amplitude [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. The rationale for rDBS is to provide stimulation only when necessary (i.e., when a patient is or would be experiencing symptoms).…”
Section: Introductionmentioning
confidence: 99%
“…Several rDBS studies in individuals with ET have focused on implanted electrocorticography strips [17,20,32] or local field potentials (LFP) recorded from the J o u r n a l P r e -p r o o f depth lead [22]. These studies largely depended on movement-related beta (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) desynchronization to control stimulation [17,20,32]. Additionally, studies using recordings from externalized leads in the postoperative period have demonstrated that tremor provoking movements may be decoded using both theta (4-7 Hz) and beta bands [22].…”
Section: Introductionmentioning
confidence: 99%
“…However, the studies reported a negative relationship between increased power in this low frequency band and movement speed especially when patients were off medication, which conflicts with some of the previous literature. More recently, Molina et al (2021) reported a low frequency (1-8 Hz) power triggered closed loop PPN DBS study and showed a 40% improvement in medication-refractory freezing of gait (FoG) in three out of five PD patients with FoG. However, there is no comparison of the low frequency power triggered closed loop PPN DBS against continuous PPN DBS, so it is still difficult to establish the relationship between the low frequency oscillations in the PPN and gait.…”
Section: Introductionmentioning
confidence: 99%